Impaired contextual fear conditioning in RasGRF2 mutant mice is likely Ras-ERK-dependent - Olevska, Anastasia; Spanagel, Rainer; Bernardi, Rick E. (Neurobiology of learning and memory, 2021)
Ras/Raf/MEK/ERK (Ras-ERK) signaling has been shown to play an important role in fear acquisition. However, little information is known regarding the mechanisms that contribute to the regulation of this pathway in terms of the learning of conditioned fears. Ras Guanine Nucleotide Releasing Factor 2 (RasGRF2) is one of two guanine nucleotide exchange factors (GEF) that regulates the Ras-ERK signaling pathway in a Ca2+-dependent manner via control of the cycling of Ras isoforms between an inactive and active state. Here we sought to determine the role of RasGRF2 on contextual fear conditioning in RasGRF2 knockout (KO) and their wild type (WT) counterparts. Male KO and WT mice underwent a single session of contextual fear conditioning (12 min, 4 unsignaled shocks), followed by either daily 12-min retention trials or the molecular analysis of Ras activation and pERK1/2 activity. KO mice showed an impaired acquisition of contextual fear, as demonstrated by reduced freezing during fear conditioning and 24-hr retention tests relative to WT mice. Ras analysis following fear conditioning demonstrated a reduction in Ras activation in the hippocampus as well as a reduction in pERK1/2 in the CA1 region of the hippocampus in KO mice, suggesting that the decrease in fear conditioning in KO mice is at least in part due to the impairment of Ras-ERK signaling in the hippocampus during learning. These data indicate a role for RasGRF2 in contextual fear conditioning in mice that may be Ras-ERK-dependent.
Gesehen am 22.09.2021